ANALISIS PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM PENGELOLAAN LIMBAH B3 TANPA IZIN (STUDI PUTUSAN NOMOR 533/Pid.B/LH/2021/ PN TNG) - Farida Nurun Nazah; Salwa Putri Septiana; Mochamad Yulian Fadhli Saputra; Akmalia Salsabila; Claraditha Adelia Nelson; Owen Novail Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines a court decision concerning an environmental case involving PT Cisadane Raya Chemicals, represented by Johny Sanggam Edison. The case focuses on improper management of hazardous and toxic waste (B3), which created potential environmental pollution. The research applies a normative juridical approach by analyzing the judge’s decision, evidence, and the prosecutor’s claims. The findings indicate that the defendant was legally proven to have violated regulations regarding hazardous waste management. The panel of judges imposed a criminal sanction in the form of a fine and ordered certain evidence to be confiscated or destroyed in accordance with the law. This decision highlights the importance of corporate compliance with environmental regulations and legal responsibility in protecting the environment. Furthermore, it serves as a form of law enforcement aimed at creating a deterrent effect for business actors to prevent similar violations in the future.